ABKS‐CSC: attribute‐based keyword search with constant‐size ciphertexts. Issue 18 (26th October 2016) - Yang, Ye; Han, Jinguang; Susilo, Willy; Yuen, Tsz Hon; Li, Jiguo
Abstract: Attribute‐based keyword search (ABKS) was proposed to enable a third party to search encrypted keywords without compromising the security of the original data. Because it can express flexible access policy, ABKS has attracted a lot of attention. Existing ABKS schemes mainly focused on the expression of access structures, while the computation cost and communication cost are linear with the number of required attributes. Therefore, existing ABKS schemes are unsuitable to the devices that have constrained space and computing power, such as smart phone and tablet. In this paper, an ABKS with constant‐size ciphertext scheme is proposed. The proposed scheme captures the following nice features: (1) The index encryption algorithm has constant computation cost; (2) the searchable ciphertexts are constant size; (3) the trapdoors for keywords are constant size; and (4) the test algorithm has constant computation cost. To the best of our knowledge, it is the first time that an ABKS with constant‐size ciphertext scheme is proposed. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In this paper, an attribute‐based keyword search with constant‐size ciphertext scheme is proposed. The proposed scheme captures the following nice features: (1) The index encryption algorithm has constant computation cost; (2) the searchable ciphertexts are constant size; (3) the trapdoors for keywords are constant size; and (4) the test algorithm has constant computation cost. To the best of our knowledge, it is the first time that an attribute‐based keyword search with constant‐size ciphertext is proposed.